DAMPAK POSITIF DAN NEGATIF SOSIAL MEDIA TERHADAP PERUBAHAN SOSIAL ANAK: DAMPAK POSITIF DAN NEGATIF SOSIAL MEDIA TERHADAP PERUBAHAN SOSIAL ANAK - Sulidar Fitri (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2017)
Children of primary school age today is learning quickly in The use of technological devices that many adult people use such as a mobile phone or laptop connected to the Internet network so it’s provide easy access to an incredible wide world to a variety of sites and applications that are provided in free of charge, Social media technologies indicate social change among children of primary school age in terms of social activities or relationships between human beings. The method of collecting data in this study were collected by observation at the school, in this case also has done an interview to the principal and students of class VI SDN Tugu 3 Gunung Java Cihideung Tasikmalaya, the number of students who were interviewed as a whole amounted to 65 people, this study obtained their personal indication of antisocial child because too preoccupied with social media being used.